Hazard identification risk assessment and risk control (HIRARC) of safety junior supervisor in a construction company - Leonardo Leonardo; Elty Sarvia (Journal Industrial Servicess, 2022)
Company Y is a construction company in the fabrication business by working on projects with sub-classifications, namely foundation work including transmitters, roofing and waterproofing work, concrete work, and steel work and its installation. The company also produces machines used to process palm oil, such as threshers, screw conveyor belts, and sterilizers. This company found 15 cases of work accidents occurred from 2017-2020. The purpose of this study is to analyze the causes of frequent accidents and analyze potential hazards and assess the risk of hazards in the company so that it can provide recommendations for appropriate control for the company using the hazard identification risk assessment and risk control (HIRARC) method. There are 5 types of accidents that have occurred frequently and 13 potential accident hazards in the company today. Then for the risk level in the risk assessment, there is 1 event with a high-risk rating (in red), 10 events with a medium level risk rating (yellow), and 11 events with a low-risk rating result (in green). The risk of accidents that should be a priority is the risk of gas cylinder leakage accidents. Accident data for 3 years are depicted in a Pareto diagram and analyzed the cause based on a fishbone diagram, using factors 4M+1E, namely humans, machines, methods, raw materials, and the environment.